Impact of ghrelin on vitreous cytokine levels in an experimental uveitis model - Turgut, Burak; Gul, Fatih Cem; Dagli, Ferda; Ilhan, Nevin; Ozgen, Metin (Dove Medical Press Ltd, 2013)
Background: The purpose of this study was to investigate the effect of intraperitoneal ghrelin on vitreous levels of interleukin (IL)-1, IL-6, and tumor necrosis factor-alpha (TNF-alpha) and to compare its effects with those of intraperitoneal infliximab in an experimental uveitis model. Methods: Twenty-four male rats were assigned to four groups of six rats in each. All the rats, except for those in group 1 (controls), were injected intravitreally with concanavalin A to induce experimental uveitis. Rats in group 2 (sham) were not given any treatment after uveitis was induced. Rats in group 3 were given intraperitoneal infliximab 0.5 mg/100 mL on days 0, 1, 3, 5, and 7 following induction of uveitis on day 14 of the study. Rats in group 4 were given intraperitoneal ghrelin 10 ng/kg/day for 7 days following induction of uveitis. On day 21 of the study, enucleated globes were subjected to histopathologic examination. Vitreous levels of IL-1, IL-6, and TNF-alpha were measured by enzyme-linked immunosorbent assay. Results: Vitreous levels of IL-1, IL-6, and TNF-alpha were significantly increased in the sham group relative to the control group (P < 0.05), but showed a significant decrease in the group treated with infliximab (P < 0.05). Cytokine levels also decreased in the ghrelin-treated group, but the decrease was not statistically significant (P > 0.05). Conclusion: Ghrelin failed to decrease the IL-1, IL-6, and TNF-alpha levels that play a critical role in the pathogenesis of uveitis.
Keywords: uveitis; tumor necrosis factor-alpha; interleukin-1; interleukin-6; infliximab; ghrelin